2016
DOI: 10.1136/bmjopen-2016-011069
|View full text |Cite
|
Sign up to set email alerts
|

Older, vulnerable patient view: a pilot and feasibility study of the patient measure of safety (PMOS) with patients in Australia

Abstract: ObjectivesThe UK-developed patient measure of safety (PMOS) is a validated tool which captures patient perceptions of safety in hospitals. We aimed (1) to investigate the extent to which the PMOS is appropriate for use with stroke, acute myocardial infarction (AMI) and hip fracture patients in Australian hospitals and (2) to pilot the PMOS for use in a large-scale, national study ‘Deepening our Understanding of Quality in Australia’ (DUQuA).ParticipantsStroke, AMI and hip fracture patients (n=34) receiving car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…communication and team work, organisation of care planning, information flow resonate strongly with themes arising in this review. However, whilst PMOS have been explored within other hospital settings [55], this review has profiled areas of safety particular to intensive care e.g. family visiting and staff competence and from the perspective of family members.…”
Section: Discussionmentioning
confidence: 99%
“…communication and team work, organisation of care planning, information flow resonate strongly with themes arising in this review. However, whilst PMOS have been explored within other hospital settings [55], this review has profiled areas of safety particular to intensive care e.g. family visiting and staff competence and from the perspective of family members.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to produce two revised patient measures of safety that are practical, feasible and simple for patients to complete, responding directly to the need to enhance patient acceptability of the original measure 19 20. PMOS-30 included less negatively worded items compared with PMOS-44 (37% as opposed to 57%), and the internal reliability of PMOS-30 was established.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a formative evaluation of the implementation of PRASE with hospital volunteers—volunteers described how the measure was too time consuming for patients to complete, and that its length impacted on the conversation and rapport they were able to build with patients 19. Furthermore, in recognition of the potential difficulties described above, researchers in Australia have produced a revised version of the measure for use with vulnerable older adult groups 20…”
Section: Introductionmentioning
confidence: 99%
“…This choice was justified based on previous studies with adult, older adult and acute hospitalized patients, in which it was found that simple questions would be more effective. 33 In the transcultural adaptation process of the PMOS to Brazilian Portuguese, no difficulties were found related to the negatively worded items; therefore, they were maintained as in the original instrument.…”
Section: /16mentioning
confidence: 99%